Single Menu-Based Interface for Users: Designing a Prototype Framework - Mandal, Sukumar (Journal of Information and Knowledge, 2020)
This paper attempts to introduce the process of designing a digital library with the feature of a single menu based interface, using open source digital library software DSpace and open source standard Dublin Core metadata. DSpace is widely used digital library software used in different institutes, universities and archives, etc. Dublin Core metadata is a popular open source standard, used for the creation and modification of metadata of digital content. Single menu-based interface is designed using the Ubuntu operating system and this framework helps in carrying out important functions related to digital library system’s core technical aspects, without any hassle.